Knowledge of the human papilloma virus vaccines, and opinions of gynaecologists on its implementation in Nigeria (2013)
The objective of this study was to determine the knowledge and perception of Nigerian Obstetricians and Gynaecologists towards human papilloma virus vaccine use in Nigeria. A cross sectional study was conducted amongst participants that attended the 42nd Society of Gynaecology and Obstetrics of Nigeria. The findings revealed that 44.5% knew the correct HPV vaccine schedule. Regarding implementation in Nigeria, 87.4% suggested its incorporation into the national immunization program and about a third agreed that it should be a precondition for school enrollment. Regression analysis showed that senior residents were more likely to have adequate knowledge of the vaccine compared to junior residents (AOR 7.181 95% CI OR=1.792 – 28.782). We conclude that the knowledge of eligibility and schedule is poor. It is recommended that adequate information should be provided to this group of health workers because of their strategic position in its implementation in Nigeria.